Local norepinephrine value in the control of bleeding by acute gastric ulcers - Campos Pierri, Néstor; Villar, Miguel; Reyes, Ismael; Varela, José Alberto; Yametti, Luis; Bonaba, Roberto; Gomez Fossati, Carlos (Cirugía del Uruguay, 1975)
An experimental model of acute gastric ulcer was reproduced in 24 dogs, according to the procedure: deviced by Le Veen. Animals were grouped into 3 equal series of 8 dogs each. One of the series was used as control and the other 2 were treated with a norepinephrine solution ( at different concentrations and during different times) in a topic, endogastric -way in an attempt to arrest the bleeding. lt was proved that, at a 16 mg/lt concentration, the drug gives a number of survivors which is higher than that of the non-treated animals, without undersirable side-effects.